The Influence of Pulsed Electron Beam Processing on the Quality of Working Surfaces of Titanium Alloy Products - Undrakh Mishigdorzhiyn; Aleksey Pyatykh; Andrey Savilov; Nikolay Ulakhanov; Ivan Galetsky; Kirill Demin; Alexander Tikhonov; Maxim Vorobyov; Elizaveta Petrikova; Shunqi Mei (Lubricants)
Titanium alloys are widely used in medicine due to their unique properties, including inertness with respect to living tissues, light weight, high strength, and impact toughness. For successful implementation, titanium alloy implants should possess high wear resistance and hydrophilicity. This article investigates the surface modification process of VT-1 and VT-6 titanium alloys by electron-beam processing (EBP). The EBP effect on the modified surface′s wear resistance, roughness, and hydrophilicity was analyzed. The specimens were made by machining them at a CNC turning center. The specimen surfaces were modified at the SOLO facility by a submillisecond modulated electron beam with a controlled power density of thermal impact, allowing it to reach and stabilize 1400 °C in 400 µs and then maintain it on the surface for 600 µs. A friction machine with a counterbody was used to study the wear resistance of the specimen surface. The study revealed that EBP reduces the roughness parameters of the surface. EBP also decreases the contact angle of wetting, indicating an increase in hydrophilicity compared to the original surface. Experimentally, it was shown that the formation of a nanostructure consisting of needle-like α-strips induced by EBP improves the wear resistance of the surface layer.